APLIKASI REFRIGERAN CAMPURAN LPG/CO2 PADA SISTEM REFRIGERASI KOMPRESI UAP - Nasrul Ilminnafik (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2012)
A new binary mixture of R744 and R290 as an alternative natural refrigerant to halocarbon was presented in this paper. Its environmental performance is friendly. It has an ODP of zero and GWP smaller than 20. This work investigates the result of an experimental study carried out to determine the performance of a refrigeration system. Experimental studies for this mixture were performed on machine installation A.C. Bench, P.A. Hilton. Ltd.. Serial No. A573/41154. LPG-CO2 mixing ratio used was 90:10; 85:15; 80:20% by mass, with the total mass of the mixture of 300 grams. The results showed that the increase of air velocity at the evaporator with CO2 concentrations is constant, which is causing the increase on refrigeration capacity. While the addition of CO2 concentration mixed refrigerant causing decrease on refrigeration capacity. This is due to the increasing CO2 concentration causes a decrease in enthalpy of the mixture, which causes the refrigeration capacity is also decreased. Increased of air flow velocity at the evaporator at a concentration of CO2 remains causing compressor work resulting decrease. This is due to an increase in air velocity causing an increase in temperature of the evaporator so that the required compressor work is decrease. Increase of concentration of CO2 in the mixture causes the compressor work increases because CO2 has a high-pressure work so that the compression load is increasing and the compressor were employment given compressor is also increasing. Increase of air flow rate causes the coefficient of performance of refrigeration systems is getting increased. While the increase in CO2 concentrations has led to the decrease of performance coefficient Keywords: Hydrocarbon refrigerant, LPG, CO2, coeffisient of performance.